Mesenteric panniculitis - a rare disorder: radiological features - Dev, Ghanshyam; Gupta, Anshita; Ilyas, Mohd (The European Research Journal, 2019)
Objectives: The main objective of this study was to assess the key  computed tomographic features of various types of mesenteric panniculitis and to assess their etiology.Methods: In this retrospective study, the radiological scans of seven patients were evaluated, the computed tomographic features and etiology were assessed. The Coulier's criteria were used for the radiological inclusion of a patient as a case of mesenteric panniculitis.Results: Four of the patients had a history of some procedure or surgery performed 6 weeks to six months before presenting with panniculitis. Two of the seven cases were idiopathic while the seventh case presented after an episode of pyonephrosis. Mesentric panniculitis is one of the broad range of disorders that may result in imaging finding of misty mesentry on computed tomography. The key computed tomography finding seen in all these cases was  regional increase in mesenteric fat density that was seen at abdominopelvic computed tomography. Conclusion: Computed tomography has a particular picture in the cases of mesenteric panniculitis and forms one of the most sensitive non-invasive modality of investigation in the diagnosis of mesenteric panniculitis.